Saikosaponin D Inhibited IL-1β Induced ATDC 5 Chondrocytes Apoptosis In Vitro and Delayed Articular Cartilage Degeneration in OA Model Mice In Vivo - Wu, Xinhui; Zhao, Kangxian; Fang, Xiaoxin; Lu, Feng; Cheng, Pu; Song, Xiaoting; Zhang, Weikang; Yao, Can; Zhu, Jiling; Chen, Haixiao (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is the most common joint diseases in the elderly, characterized by cartilage degradation and proliferation of subchondral bone. The pathogenesis of OA involves a variety of inflammatory mediators, including nitric oxide (NO), prostaglandin E2 (PGE2), tumor necrosis factor (TNF)-α and interleukin (IL)-1β. From the molecular mechanism, nuclear factor-erythroid 2-related factor (Nrf2)/ heme oxygenase-1 (HO-1) pathway and the expression of ROS regulated the production of the above inflammatory mediators. Saikosaponin D(SSD) which is an active ingredient isolated from Bupleurum has various biological function. In this study, IL-1β was used as a pro-inflammatory factor to create an in vitro OA model. According to the results of high-density culture, qPCR, ROS measurement, western blot, and immunofluorescence, SSD activated the Nrf2/HO-1/ROS axis, inhibited the production of inflammatory mediators, and protected against ECM destruction. The DMM mouse model was used as a model of OA in mice. From the results of safranin O/fast green staining, hematoxylin–eosin staining, tartrate-resistant acid phosphatase (TRAP) staining and OARSI scores, SSD protected against the mice knee articular cartilage degeneration and reduced the number of osteoclasts in the subchondral bone. Experimental results found that SSD suppressed IL-1β induced ATDC 5 chondrocytes apoptosis via Nrf2/HO-1/ROS axis in vitro. SSD delayed the progression of OA in DMMs model mice in vivo. Therefore, SSD ha s the potential to become a drug for clinical treatment of OA.